FACTORS AFFECTING INCOMES OF INFORMAL SECTOR IN DISTRICT JEMBER (Case Study on Garment Traders) - Sugiantono A.R. (STIE Mandala Jember, 2012)
The role of street hawkers contribute greatly to the abundant employment and overcome poverty. But so far faced limited access fo resources to ensure its survival, The question is how far vendors attempt to provide the economic welfare of fishermen families. Research conducted on street vendors, especially garment traders in Jember is concluded that: (1) the factors that affect the income of street vendors is the number of dependent family members and the amount of venture capital. Revenues trade sidewalk to meet minimum living needs (KHM) household,